Stereoisomer concentrations of amphetamine, amphetamine derivatives and metabolites in saliva and urine in comparison with blood plasma levels utilizing a validated stereoselective gas chromatography ion-trap mass spectrometry assay · - Hua, Gan Siew (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
Amphetamine-type stimulants (ATS) are a family of drugs classified as entactogens which posses both stimulant and hallucinogenic properties. Abuse of ATS is an increasingly serious problem worldwide. The abuse of ATS results in several negative side-effects including hyperthermia, elevated' heart rate and blood pressure, delirium and psychotic behavior. Longterm abuse leads to extensive hepatotoxicity and neurotoxicity. ATS are chiral molecules and metabolism of these drugs exhibits significant stereoselectivity. It has been shown that each individual ATS enantiomer exhibits a unique pharmacokinetic and pharmacodynamic profile. In this study, a novel assay for sensitive and selective stereospecific determination of amphetamine-type s1imulants was developed. The assay involves a simultaneous extraction and chiral derivatization step followed by analysis by gas chromatography-mass spectrometry. THis resulted in an assay that was rapid and simple to perform. Using an fractional factorial experimental design approach, the method was optimized and validpted. The method was applied to samples from known ATS abusers and the stereoselectivity for the elimination of ATS in biological samples was characterized. This study resulted in a novel method for the determination of ATS in biological samples, which will be applied in further studies on the stereoselective metabolism of ATS.